2010
DOI: 10.1074/jbc.m110.114736
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA (miRNA)-mediated Interaction between Leukemia/Lymphoma-related Factor (LRF) and Alternative Splicing Factor/Splicing Factor 2 (ASF/SF2) Affects Mouse Embryonic Fibroblast Senescence and Apoptosis

Abstract: Leukemia/lymphoma-related factor (LRF) is a transcriptional repressor, which by recruiting histone deacetylases specifically represses p19/ARF expression, thus behaving as an oncogene. Conversely, in mouse embryonic fibroblasts (MEF), LRF inhibition causes aberrant p19ARF up-regulation resulting in proliferative defects and premature senescence. We have recently shown that LRF is controlled by microRNAs. Here we show that LRF acts on MEF proliferation and senescence/apoptosis by repressing miR-28 and miR-505, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 60 publications
2
45
1
Order By: Relevance
“…(A) Quantitative RT-PCR analysis of total endoglin, the intron responsible for S-endoglin and PAI-1, an endothelial senescence marker (Comi et al, 1995;Erusalimsky, 2009) demonstrated in endothelial cells (Figs 5 and 6), suggesting that the splicing factor ASF ⁄ SF2 is a new target of senescence. This is in line with the reported role of ASF ⁄ SF2 as modulator of the senescence induced by oncogene overexpression in mouse embryonic fibroblasts (Verduci et al, 2010) as well as with the upregulation of ASF ⁄ SF2 in various human tumors and with the oncoprotein function of ASF ⁄ SF2 itself (Karni et al, 2007). Moreover, a direct correlation was established between the preferential cytoplasmic localization of ASF ⁄ SF2 and S-endoglin expression at the senescent stage of endothelial cells.…”
Section: Discussionsupporting
confidence: 75%
“…(A) Quantitative RT-PCR analysis of total endoglin, the intron responsible for S-endoglin and PAI-1, an endothelial senescence marker (Comi et al, 1995;Erusalimsky, 2009) demonstrated in endothelial cells (Figs 5 and 6), suggesting that the splicing factor ASF ⁄ SF2 is a new target of senescence. This is in line with the reported role of ASF ⁄ SF2 as modulator of the senescence induced by oncogene overexpression in mouse embryonic fibroblasts (Verduci et al, 2010) as well as with the upregulation of ASF ⁄ SF2 in various human tumors and with the oncoprotein function of ASF ⁄ SF2 itself (Karni et al, 2007). Moreover, a direct correlation was established between the preferential cytoplasmic localization of ASF ⁄ SF2 and S-endoglin expression at the senescent stage of endothelial cells.…”
Section: Discussionsupporting
confidence: 75%
“…The regulatory role of ATM in miRNA biogenesis is modulated by KH-type splicing regulatory protein (KSRP) (Zhang et al, 2011). Accordingly, it has subsequently been reported that SRSF1 is regulated by miR-505 and miR-28 in mouse embryonic fibroblasts (Verduci et al, 2010). These findings indicate that investigation of ATM , KSRP and microRNA regulation is potentially a fruitful future avenue of study.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism(s) mediating miR-28-5p induction is not known. However, the proto-oncogene zinc finger and BTB domain containing 7A (ZBTB7A, also known as LRF) has been shown to negatively regulate miR-28 expression (38) and to compete with the Sp1 transcription factor for target binding (39). Whether ZBTB7A/LRF acts downstream of pVHL to control of miR-28 expression remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%